Reassessment of Kepler’s habitable zone Earth-like exoplanets with data-driven null signal templates - Jakob Robnik; Uroš Seljak (Proceedings of the National Academy of Sciences, 2025)
One of the primary mission goals of the Kepler space telescope is to detect Earth-like terrestrial planets in the habitable zone around Sun-like stars. Unfortunately, such planets are at the detection limit. Estimating their statistical significance via false alarm probability (FAP) is crucial for their validation and has a large impact on the estimate of their occurrence rate, which is of central importance for future spectroscopic missions searching for life signatures. Current methods estimate FAP by light curve inverting or scrambling, but we show that both of these approaches are unsatisfactory. Here, we propose to modify the planet transit template by randomly shifting the transit times by small amounts. We show that the exoplanet search with the resulting null signal template (NST) has the same statistical properties as with the true periodic template, which enables assigning a reliable star-specific FAP to every candidate. We show on simulations and on the real data that the method is robust to unmodeled noise contamination. We reevaluate the statistical significance of all 47 previously proposed habitable Earth-like and super Earth Kepler candidates and assign them star-specific NST based FAP. We identify 29 candidates with FAP below 1%, 7 of whom are currently not considered confirmed. Among these are Kepler 452b with radius 1.5 R ⊕ , a period of 384 d, and KOI 2194.03 with radius 1.8 R ⊕ and a period of 445 d, both around Sun-like G stars. Several well-known candidates should be considered marginal or likely false alarms, including Kepler 186f with 20% FAP.